Thermal reliability of myristic acid/palmitic acid/sodium laurate eutectic mixture: A feasibility study of accelerated aging for thermal energy storage application - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Silakhori M. (Elsevier Ltd, 2023)
The thermal characteristic stability of myristic acid/palmitic acid/sodium laurate (MA/PA/SL) eutectic mixtures have been measured by a thermal cycling test. The phase change temperature and heat storage capacity of each eutectic were evaluated by differential scanning calorimetric (DSC) after 300, 700, and 1000 thermal cycles. The thermal properties of the MA/PA/SL eutectic mixture shows only a minor changes on melting temperature (Tm) and latent heat of fusion (?Hf) after 300, 700, and 1000 thermal cycles. The chemical structure of MA/PA/SL shows no degradation after 1000 melting/cooling cycles as well as MA/PA/SL has a better thermal performance during heating and cooling process. Therefore, it is noted that the MA/PA/SL eutectic mixture is applicable for long term use as a phase change material in thermal energy storage (TES) applications. © 2014 Published by Elsevier Ltd.